On the Dynamics of Sexually Transmitted Diseases Under Awareness and Treatment - Oukouomi Noutchie, Suares Clovis; Mafatle, Ntswaki Elizabeth; Guiem, Richard; M'pika Massoukou, Rodrigue Yves (Frontiers in Applied Mathematics and Statistics, 2022)
In this paper, we develop and extend the work of Jia and Qin on sexually trans- mitted disease models with a novel class of nonlinear incidence. Awareness plays a central role both in the susceptible and the infectious classes. The Existence, uniqueness, boundedness, and positivity of solutions are systematically established. Concavity arguments and the occurrence of a vertical asymptote are essential in the proof of the existence of a unique endemic equilibrium. Conditions for the stability of all steady states are investigated. In particular, numerical simulations are performed in order to capture the asymptotic behavior of solutions.